Sliding Mode Control-Based Chaos Stabilization in PM DC Motor Drive - Abdullah, Mohammed Abbas; Tahir, Fadhil Rahma; Abdul-Hassan, Khalid M. (Iraqi Journal for Electrical and Electronic Engineering, 2017)
In this paper, a model of PM DC Motor Drive is presented. The nonlinear dynamics of PM DC Motor Drive is discussed. The drive system shows different dynamical behaviors; periodic, quasi-period, and chaotic and are characterized by bifurcation diagrams, time series evolution, and phase portrait. The stabilization of chaos to a fixed point is adopted using slide mode controller (SMC). The chaotic dynamics are suppressed and the fixed point dynamics are observed after the activation of proposed controller. Numerical simulation results show the effectiveness of the proposed method of control for stabilization the chaos and different disturbances in the system.